ORIENTACIONES PSICOPEDAGÓGICAS Y SU INFLUENCIA EN EL PROCESO DE ENSEÑANZA-APRENDIZAJE DE LOS ESTUDIANTES DE SÉPTIMO AÑO DE LA ESCUELA DE EDUCACIÓN BÁSICA LOS ÁNGELES EN EL AÑO 2023. - BACILIO CRUZ ROBERT JAREN (2024)
The research focused on evaluating the impact of psychopedagogical orientations on the teaching-learning process of seventh-grade students at School of Basic Education Los Ángeles. A mixed approach was used, including surveys, interviews, and classroom observations. Before the implementation of the orientations, both students and the teacher showed limited knowledge about them. However, after their application, significant improvements were observed in several aspects. The emotional climate and teacher-student relationship were strengthened, creating an environment of greater respect, trust, and mutual support. Adaptation and diversification of teaching were highlighted, using strategies that addressed the different learning styles and skill levels of students. Additionally, critical thinking and problem-solving were promoted, encouraging active student participation in these activities; furthermore, inclusion and attention to diversity were improved, adapting materials and activities to ensure the participation of all students. These results suggest that psychopedagogical orientations have a positive impact on teaching practice and student learning. It is recommended to continue teacher training in these orientations, as well as the implementation and periodic evaluation of psychopedagogical strategies to improve the educational process overall.